Co‐diffusion from solid sources for bifacial n‐type solar cells. Issue 9 (1st August 2013) - Rothhardt, Philip; Keding, Roman; Wolf, Andreas; Biro, Daniel
Abstract We present a simplified process sequence for the fabrication of large area n‐type silicon solar cells. The boron emitter and full area phosphorus back surface field are formed in one single high temperature step using doped glasses deposited by plasma enhanced chemical vapour deposition (PECVD) as diffusion sources. By optimizing the gas composition during the PECVD process, we not only prevent the formation of a boron rich layer (BRL), but also achieve doping profiles that exhibit a low dark saturation current density while allowing for contact formation by screen printing. The presented co‐diffusion process allows for major process simplification compared to the state of the art diffusion process relying on multiple high temperature processes, masking and wet chemistry steps. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Solar cell based on n‐type silicon featuring a co‐diffused boron emitter and phosphorus back‐surface field (BSF). (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)